File Service Architecture for Heterogeneous Clients - Sanober, Sumaya; Waheed, Amtul (International Journal of Computer Sciences and Engineering, 2025)
Internet usage has gone far beyond expectation and continues to grow. Services on the Internet are also more innovative than ever before. Many more different system architectures are currently used to obtain the same pool of services. Now, the trend is to make uniform architecture to provide services. SOA is a service that aims to integrate and be interoperable with various implementation languages. SOA is a concept of distributed computing, the best example of which is file sharing. Remote sharing remains an issue. Although many services are available to provide remote file sharing, they have problems in accessing file with ease, user friendliness, a generic communication protocol, a secured method to communicate during transferring and traversing the secured firewalls. This paper focuses on how easily the file can be shared with the generic communication protocol and a secured method by bypassing the issues of NAT. To provide such service, we do not have any option other than XML, which enables the system to service the end users, who can choose to download or upload files using a browser or an application client. Thus, we have built a middleware for file sharing. The middleware and the application client are equipped with the NAT facilities to traverse the firewalls. Our proposed middleware can service the users of both systems (Browser and Application client). The performance of the proposed system for remote sharing suggests using XML as an interface to implement the SOA-based applications.